A review of mesoporous silica nanoparticles for targeted drug delivery, characterization and synthesis - Mohan, Shimi; Jarin, T.; Deepanraj, B. (Edelweiss Applied Science and Technology, 2025)
Mesoporous silica nanoparticles (MSNs) possess uniform pore dimensions, excellent thermal stability, and are functionalized with various chemical groups, making them a reliable choice for diverse applications, including medicine, supercapacitors, food toxicity detection, and the chemical industry. MSNs are primarily chosen as drug carriers due to their unique tunability features, inert and porous nature, and resistance to chemical degradation. Compared to high-purity silica produced using synthetic organic precursors, MSNs are relatively cost-effective owing to their simple synthesis process. This paper reviews the properties, preparation, and synthesis of MSNs, as well as their applications in drug loading methodologies. These applications include tumor detection, food purification, biosensors, and drug delivery. The final section of the review discusses the effectiveness of MSNs and their interactions with biological systems, along with various issues that need to be addressed.